2008
DOI: 10.1002/jmv.21098
|View full text |Cite
|
Sign up to set email alerts
|

Transmission routes of hepatitis B virus infection in chronic hepatitis B patients in The Netherlands

Abstract: The Netherlands is a low endemic country for hepatitis B virus (HBV). Rotterdam, a city in The Netherlands harbors a large group of chronic hepatitis B (CHB) patients of which most are born abroad. The study included 464 consecutive CHB patients who were reported to the Municipal Public Health Service in Rotterdam from January 1, 2002 to September 15, 2005. The HBV genotypes, possible transmission routes of infection and travel history of CHB patients born in The Netherlands, were compared with those CHB patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…This form of transmission is the most frequent in countries with low endemicity, as is the case of most European countries, as confi rmed in a survey carried out in Holland. 22 Excessive alcohol intake is predominant among males (58.9%; p < 0.001). In other studies, especially from Holland, it was concluded that males showed greater prevalence of alcoholism than females (9.5% and 3.6%, respectively).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This form of transmission is the most frequent in countries with low endemicity, as is the case of most European countries, as confi rmed in a survey carried out in Holland. 22 Excessive alcohol intake is predominant among males (58.9%; p < 0.001). In other studies, especially from Holland, it was concluded that males showed greater prevalence of alcoholism than females (9.5% and 3.6%, respectively).…”
Section: Discussionmentioning
confidence: 98%
“…14,15 In countries where endemicity is low, and in age groups not covered by mandatory vaccination, sexual transmission is more common among males, whereas intrafamilial transmission seems to predominate among females. 14,22 Vaccination is mandatory for all newborns in Portugal since 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Discovery of “pure” genotypes E, G or H strains would confirm this hypothesis. Most of the studies that have found a high prevalence of both D and E were reported in Europe, in particular France 92–95,103 . The only country less affected by recent migration is Cameroon, where these two variants might have been endemic for a longer period of time.…”
Section: Hbv Recombinationmentioning
confidence: 99%
“…Most of the studies that have found a high prevalence of both D and E were reported in Europe, in particular France. [92][93][94][95]103 The only country less affected by recent migration is Cameroon, where these two variants might have been endemic for a longer period of time. However, sequencing of a number of Cameroonian HBV/E strains to date did not reveal any evidence of the presence of a "pure" genotype E that is not "sharing" its core gene sequence with genotype D. 21,22 Genotypes G and H have the highest prevalence in Mexico, 133,134 a country where genotypes A and F are also prevalent.…”
Section: Hbv Recombinationmentioning
confidence: 99%
“…Moreover, because China has the largest population in the world, the demand for blood transfusion during surgery, as well as other blood-related products for medical needs, is extremely high. Therefore, HBV infection caused by blood transfusion or from the use of HBV-contaminated blood products is another major transmission route, in addition to transmission via sexual contact, drug injection and vertical transmission from an infected mother to an unborn baby (Buddeberg et al, 2008;Toy et al, 2008). This is especially true when the blood was collected from an HBV-infected donor during a period when it could not be detected, or when the donor was infected by a mutated HBV strain that can lead to false negative results during routine HBV screening (Candotti and Allain 2009).…”
Section: Introductionmentioning
confidence: 99%